Effects of Galactomannan Oligosaccharides on Growth Performance, Mycotoxin Detoxification, Serum Biochemistry, and Hematology of Goats Fed Mycotoxins-Contaminated Diets - Wu, Yicheng; Ren, Ao; Lv, Xiaokang; Ran, Tao; Zhang, Guijie; Zhou, Chuanshe; Tan, Zhiliang (Frontiers in Veterinary Science, 2022)
This study was conducted to investigate the protective effects of mycotoxin adsorbent galactomannan oligosaccharides (GMOS) on growth performance, fermentation parameters, mycotoxins residues, serum biochemistry and oxidative stress parameters of the goats. The in vitro test indicated that 0.05% GMOS outperformed yeast cell wall (YCW) and montmorillonite (MMT) in aflatoxins absorption. Then 20 3-month-old Xiangdong black goats (15.0 ± 1.9 kg) were randomly divided into two dietary treatments for the animal test. The control group (CON group) was fed a multi-mycotoxins contaminated diet, whereas the experimental group (GMOS group) received multi-mycotoxins contaminated diet plus 0.05% GMOS. The trail lasted for 60 days, with 12 days of adaptation period and 48 days of formal experiment period. There were no treatment effects (P > 0.10) on growth performance, serum antioxidant capacity and activities of serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP). The concentrations of zearalenone in the rumen were lower (P < 0.05) in the GMOS group. GMOS significantly reduced (P < 0.05) propionate concentration in the cecum, resulting in a rise (P < 0.01) in acetate/propionate ratio in GMOS as compared to CON. Goats of GMOS exhibited considerably greater (P < 0.05) levels of creatine kinase but lower (P = 0.02) levels of creatinine than CON. Compared with CON, GMOS supplementation significantly increased (P < 0.05) platelet count (PLT), platelet volume distribution width (PDW), and platelet hematocrit (PCT), while decreased (P < 0.05) albumin content (ALB). The 0.05% GMOS protected goats in ruminal fermentation parameters, mycotoxins residues and serum biochemistry. Moreover, GMOS had no adverse effect on goat health. To our knowledge, this is the first report of GMOS in small ruminants. These findings suggested the feasibility of dietary GMOS as a health-maintaining addictive in goat diets.